Glossary of terms content words as used in food and beverage services (FBS) NC II assessment scripts of Oton National high School grade 12 FB1 NCII learners - Villanueva, Aivon T (University of the Philippines Visayas, 2018)
One hundred and thirty-five (135) Food and Beverage Services NC II Assessment Scripts of Grade 12 Technical Vocational Livelihood (TVL) learners specializing in Food and Beverages Services (FBS) NC II were examined to come up with the glossary of terms used by FBS NC II learners of Oton National High School for the school year 2017-2018. The script has nine parts: (1)Preparing dining area and cleaning and checking table (2) Preparing and setting up the table (3) Welcoming and seating the guest (4) Taking and processing orders (5) Serving food orders (6) Providing room service (7) Setting up trays and trolleys (8) Presenting and serve food and beverage orders to guests (9) Clearing room service equipment. These are based on the competencies which must be learned in the Food and Beverages Services (FBS) area of specialization in the Technical Vocational Livelihood (TVL) track. Content words and their usage in the assessment scripts were considered, resulting in a glossary of common terms used by the learners, which contain words and expressions that are inappropriately or incorrectly used. While the glossary could add to the vocabulary reservoir used in the field of Food and Beverage Services as offered in the Senior High School curriculum, they reflect the learner's inadequate or unsuccessful transfer of the knowledge in the production level. The study points out the need for teachers of language and of specialized areas to coordinate towards integrated and effective language use.